Influence of the Multiplicity Yerba Mate Brewing on the Antioxidant Activity of the Beverages - Dmowski, P.; Post, L. (Scientific Journal of Gdynia Maritime University, 2018)
Infusions prepared from yerba mate are good sources of antioxidants, especiallypolyphenols, that are very important to its healthy and sensory properties. The presenceof these compounds largely depends on the method and multiplicity of brewing. The aimof this work is to evaluate the influence of the multiplicity of brewing on the antioxidant activityof yerba mate beverages prepared from Ilex paraguariensis. It was found that eachsubsequent yerba mate brewing reduces the antioxidant properties of beverages. It was foundthat each subsequent yerba mate brewing statistically important reduces the total content ofpolyphenols. The change in total polyphenols content was reduced even by approximately85%.